2012
DOI: 10.1097/ajp.0b013e31823e15cb
|View full text |Cite
|
Sign up to set email alerts
|

A Double-blind, Placebo-controlled Study on the Effect of Buprenorphine and Fentanyl on Descending Pain Modulation

Abstract: The opioids buprenorphine and fentanyl significantly potentiate the effect of descending pain inhibition in healthy volunteers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 51 publications
5
46
0
Order By: Relevance
“…20,21 The present study extends these findings by showing a reduced CPM response in patients with high pain sensitivity compared with patients with less pain sensitivity. Although reduced CPM was found in the high pain sensitivity group with cuff algometry (PPT and pain tolerance limit), the results also showed a significant increase in the widespread PPT during the CPT and in cuff pressure pain tolerance after the CPT in both groups.…”
Section: Cpmsupporting
confidence: 82%
See 1 more Smart Citation
“…20,21 The present study extends these findings by showing a reduced CPM response in patients with high pain sensitivity compared with patients with less pain sensitivity. Although reduced CPM was found in the high pain sensitivity group with cuff algometry (PPT and pain tolerance limit), the results also showed a significant increase in the widespread PPT during the CPT and in cuff pressure pain tolerance after the CPT in both groups.…”
Section: Cpmsupporting
confidence: 82%
“…[10][11][12] Chronic musculoskeletal pain conditions in which the degree of hypoalgesia after the cold pressor test (CPT) is reduced include fibromyalgia, [13][14][15][16][17] chronic whiplash-associated disorder, 18,19 and osteoarthritis. 20,21 Similarly, chronic musculoskeletal pain conditions with attenuated hypoalgesia after exercise include fibromyalgia (FM) [22][23][24][25] and chronic whiplash-associated disorder. 26 Other studies have reported hypoalgesia in patients with musculoskeletal pain during the cold pressor test 15,27 and after exercise.…”
mentioning
confidence: 99%
“…22,23 In a previous study from our group, based on an experimental paradigm similar to that used in the present study, the reliability of CPM was good in healthy volunteers (ICC 9 0.8). 23 This is in contrast to the poor CPM reliability observed for patients with CP in the present study. The poor test-retest most likely results not only from the nature of descending pain modulation but also from factors related to the CPM paradigm.…”
Section: Reliability Of Conditioned Pain Modulation (Dynamic Qst)supporting
confidence: 59%
“…10,23,26 Furthermore, preoperative CPM assessment has previously been shown to predict the likelihood of developing chronic postthoracotomy pain. 27 Thus, it is possible that preoperative evaluation of central pain processing in patients with CP will be useful in identifying patients who will benefit from interventional treatments (endoscopy or surgery).…”
Section: Discussionmentioning
confidence: 99%
“…In a study on opioids induced hyperalgesia, Ram et al 77 reported that CPM is reduced by opiates in patients with chronic pain. Arendt-Nielsen et al 2 reported enhancement of the CPM effect by opioids in controls. Conditioned pain modulation was not affected by lorazepam, 43 nor by oral contraceptives.…”
Section: Pharmacological and Therapeutic Applicationsmentioning
confidence: 99%